Patients' perceptions of receiving orthopaedic care during a pandemic: a patient survey. Issue 3 (12th May 2021) - Comadoll, Shea; Reams, Megan; Only, Arthur J.; Cunningham, Brian P.
Abstract : Background: Coronavirus 2019 (COVID-19) has had a great effect on the health care landscape, including altering the availability and methods of orthopaedic care. There is little information regarding patients' perceptions of orthopaedic care during the pandemic. This study was designed to assess patient concerns surrounding orthopaedic care and determine what areas can be addressed to optimize orthopaedic care during this pandemic. Methods: In the spring of 2020, during this study that was exempt from institutional review board (IRB) approval, a survey designed to evaluate the attitudes and beliefs from healthcare consumers about receiving care during the COVID-19 pandemic was sent to a group of panelists via email. Results: Three hundred sixty-six (31%) out of 1, 200 individuals completed the survey. The majority of participants expressed they would feel comfortable receiving care in orthopaedic clinics (48% immediately, 36% in 1 to 3 mo) in the immediate or near future. Participants reported they were more comfortable seeking orthopaedic care at an orthopedic urgent care facility (8% not comfortable) versus an emergency room (41% not comfortable). When thinking about receiving care at orthopaedic clinics, participants were most concerned about the risks of getting sick from other patients (18% extremely, 26% very). Seventeen percent of respondents reported that despite having orthopaedic concerns, they delayed seeking care due to COVID-19. One-third of respondents expressed a desire to know what precautions were in place to ensure safety. Conclusions: Patients remained interested in receiving orthopaedic care in the midst of a pandemic. As a result, physicians need to ensure that they effectively communicate what safety precautions are in place and what additional infection prevention measures are available. Level of Evidence: Level IV.